MXene-based SR (at) MS sponge, preparation method and application of SR (at) MS sponge in flexible wearable pressure sensor

By using MXene-based SR@MS sponge in flexible wearable pressure sensors, the problem of insufficient sensor response/recovery speed and measurement range is solved, and the pressure sensing effect with high sensitivity and a wide measurement range is achieved, with good application potential in areas such as human motion health monitoring.

CN119708614AActive Publication Date: 2025-03-28CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411894981.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-21
Publication Date
2025-03-28
Estimated Expiration
2044-12-21

AI Technical Summary

Technical Problem

The flexible wearable pressure sensor has shortcomings in response/recovery speed and measurement range, and the production process is complex, limiting its application in the fields of wearable devices and human-computer interaction. In particular, the interaction between silicone rubber and common conductive sensitive materials is weak, making it difficult to bond closely.

Method used

The MXene-based SR@MS sponge was used to coat the MXene/CB composite material on the SR@MS sponge skeleton by solution impregnation and low-temperature drying. The MXene/CB-SR@MS sponge with excellent conductivity was prepared by PDA modification and layer-by-layer self-assembly method.

Benefits of technology

It has achieved short-term rapid response/recovery of 150/180ms, has good pressure response sensitivity (7.44kPa-1) and measurement range (0~240kPa), and has shown good application potential in areas such as human sports and health monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708614A_ABST
    Figure CN119708614A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of pressure sensing, and particularly relates to an SR (silicone rubber) (at) MS (melamine sponge) sponge based on MXene, a preparation method and application of the SR (silicone rubber) (at) MS (melamine sponge) sponge in a flexible wearable pressure sensor. Carbon black nanoparticles are adsorbed on MXene through an in-situ polymerization method to prepare an MXene / CB (MXene / carbon black) composite solution, SR (at) MS sponge is prepared through PDA (polydopamine) modification and a layer-by-layer self-assembly method, the MXene / CB composite solution is soaked and dried at a low temperature, and electrodes are packaged on the upper side and the lower side of the sponge to complete preparation of the MXene / CB-SR (at) MS sponge pressure sensor. The flexible pressure sensor not only can realize short-time quick response / recovery, but also shows good pressure response, can detect the application effect of joint movement of each part of a human body, and has good application potential in the fields of human body movement health monitoring, wearable equipment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of pressure sensing, and in particular relates to a MXene-based SR@MS sponge and a preparation method thereof and an application thereof in a flexible wearable pressure sensor. Background Art

[0002] Flexible wearable pressure sensors can be attached to key parts of the body to monitor various types of human activities. Scholars have constructed flexible pressure sensors with higher sensitivity and better stability by regulating sensitive materials and designing microstructures. However, problems such as poor flexibility, slow response / recovery speed and narrow measurement range still limit the practical application of flexible wearable pressure sensors. In addition, the complex preparation process also hinders the large-scale production of flexible pressure sensors, further affecting their application in wearable devices, human-computer interaction and other fields.

[0003] Commonly used flexible materials in flexible piezoresistive pressure sensors include UV adhesives, hydrogels, and silicone elastomers. Among them, UV adhesives can significantly increase the manufacturing speed due to their fast curing characteristics, but the strain range of the prepared sensors is small and the application range is limited. Hydrogels have high stretchability and self-healing capabilities, but are easily disturbed by moisture and temperature. Silicone rubber (SR) has excellent mechanical properties, good resilience, and excellent mechanical repeatability. Moreover, SR is not affected by temperature and has good biocompatibility, making it a common material for wearable devices. However, SR has poor chemical activity, and its polarity is quite different from that of common conductive sensitive materials, resulting in weak interactions. Therefore, it is difficult for conductive sensitive materials to combine tightly with SR. Therefore, how to solve the problem that SR and common conductive sensitive materials are difficult to combine due to weak interactions has become one of the key issues in the industry. Summary of the invention

[0004] In view of this, the present invention discloses a MXene-based SR@MS sponge, a preparation method and application thereof in a flexible wearable pressure sensor.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] The first technical purpose of the present invention is to provide a MXene-based SR@MS sponge, wherein the MXene-based SR@MS sponge is a MXene / CB-SR@MS sponge, which is prepared by coating a MXene / CB composite material on a SR@MS sponge skeleton by a solution impregnation and low-temperature drying method;

[0007] The MXene / CB composite material is CB nanoparticles deposited on MXene nanosheets by electrostatic adsorption, and the MXene nanosheets are obtained by selectively etching Ti3AlC2 with a hydrochloric acid / lithium fluoride etching solution.

[0008] The second technical purpose of the present invention is to provide a method for preparing the MXene-based SR@MS sponge as described above, the method specifically comprising the following steps:

[0009] 1) Ti3AlC2 is first selectively etched with hydrochloric acid / lithium fluoride etching solution to obtain MXene nanosheets, and then a dispersed MXene solution is obtained by ultrasound and centrifugation;

[0010] 2) stirring the CB nanoparticles in deionized water, then adding the MXene solution prepared in step 1) and mixing thoroughly, heating and stirring to obtain a MXene / CB composite solution for later use;

[0011] 3) dissolving tris(hydroxymethyl)aminomethane in distilled water, and adding dopamine (DA) to stir and dissolve; placing MS in the solution, under the action of tris(hydroxymethyl)aminomethane, DA self-polymerizes on the surface of the MS skeleton and forms polydopamine PDA, thereby obtaining PDA-modified MS;

[0012] 4) The SR@MS porous sponge prepared in step 3) is immersed in the MXene / CB composite solution obtained in step 2), and then immersed in the SR / naphtha solution, dried and repeated, so as to coat the MXene / CB composite material and SR on the SR@MS sponge skeleton by a layer-by-layer self-assembly method, and finally obtain a MXene / CB-SR@MS sponge, i.e., the MXene-based SR@MS sponge.

[0013] It should be noted that SR (silicone rubber) elastic polymers are often structurally designed to further improve the mechanical properties of devices due to their flexibility and high plasticity. MXene exhibits good mechanical strength and excellent metallic conductivity. However, under air conditions, oxygen will attack the Ti atoms in MXene to oxidize MXene, thereby affecting the conductivity. Therefore, the key to improving the stability and sensing ability of MXene is to block the contact between oxygen and Ti atoms. Conductive nanomaterials are widely used in sensing, energy storage, electromagnetic shielding, and metal corrosion due to their excellent performance, and have become exciting research materials. Common conductive nanomaterials include carbon black (CB), polypyrrole, nanogold, polyaniline, etc. Among them, carbon black, as a granular material, has very good conductivity. However, it will agglomerate in organic solvents and is difficult to dissolve, making the subsequent preparation of sensors difficult. Through the in-situ polymerization method of composite materials, CB can form a continuous coating or film on various types of materials, thereby solving the problem that CB agglomerates in the solution and is difficult to attach to the sensor. By growing CB in situ in the MXene solution, CB nanoparticles can be evenly deposited on MXene nanosheets, and CB nanoparticles can act as a coat to protect Ti atoms. At the same time, the composite of two-dimensional MXene nanosheets and zero-dimensional CB nanoparticles increases the conductive pathway within the sensing layer and improves the conductivity of the sensor.

[0014] The present invention prepares a MXene / CB-SR@MS sponge flexible wearable pressure sensor by a simple method, wherein the SR@MS sponge is prepared by PDA modification and layer-by-layer self-assembly, and CB is adsorbed on the MXene solution by in-situ polymerization to prepare a MXene / CB composite solution. This flexible wearable pressure sensor can not only achieve a short-time fast response / recovery of 150 / 180ms, but also exhibits good pressure response with a sensitivity of 7.44kPa -1 , measuring range 0~240kPa. In addition, the present invention also studies the application effect of MXene / CB-SR@MS sponge sensor in detecting joint activities of various parts of the human body. The results show that MXene / CB-SR@MS sponge sensor has good application potential in the fields of human sports health monitoring.

[0015] Further, in step 1), the operation of selectively etching Ti3AlC2 with hydrochloric acid / lithium fluoride etching solution to obtain MXene nanosheets is as follows:

[0016] Ti3AlC2 was added in batches to a pre-cooled LiF / HCl solution and stirred for reaction. The solution was then washed and centrifuged until the pH value of the supernatant stabilized at 6. The resulting precipitate was dispersed in deionized water and sonicated under argon protection. The supernatant was centrifuged, separated, and collected to obtain a high-purity MXene nanosheet solution.

[0017] Furthermore, in the LiF / HCl solution, the mass ratio of lithium fluoride to hydrochloric acid is 1:(4.8-5.2); the mass ratio of the LiF / HCl solution to Ti3AlC2 is (5.2-5.5):1, and the temperature of the entire reaction mixture is maintained at 40°C-50°C, and continuous stirring is ensured within this temperature range for 24 hours.

[0018] Furthermore, in step 2), the mass ratio of the CB and MXene solutions is (0.1-0.5):5; the concentration of the MXene solution is 10 mg / mL, and the mass ratio of CB to MXene nanosheets is 2:1; the MXene / CB mixed solution is mechanically stirred for 30 minutes and then ultrasonically treated for 15 minutes.

[0019] Furthermore, tris(hydroxymethyl)aminomethane was dissolved in distilled water and the pH value was maintained at 8-9; MS was immersed in the solution at room temperature for 2 hours. Under the action of tris(hydroxymethyl)aminomethane, DA self-polymerized on the surface of the MS skeleton and formed a polydopamine (PDA) adhesion layer.

[0020] Furthermore, in step 4), in the SR / naphtha solution, the mass ratio of silicone rubber to naphtha is 1:1; the immersion time is 1 hour, the drying temperature is 60-80° C., and the drying time is 6 hours.

[0021] The third technical objective of the present invention is to provide an application of a MXene-based SR@MS sponge prepared by the method described above in a flexible wearable pressure sensor. The MXene-based SR@MS sponge can be used in a flexible wearable pressure sensor for detecting human physiological signals, and can also be used in a wearable sensor for detecting joint activities of various parts of the human body.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention prepares a MXene / CB composite solution by adsorbing CB on a MXene solution by an in-situ polymerization method, and prepares an SR@MS sponge by a layer-by-layer self-assembly method. The MXene / CB composite solution is impregnated and dried at low temperature, and electrodes are encapsulated on the upper and lower sides of the sponge to complete the preparation of the MXene / CB-SR@MS sponge pressure sensor. This flexible pressure sensor can not only achieve a short-time rapid response / recovery, but also exhibits a good pressure response, and can detect the application effect of joint activities in various parts of the human body, and has good application potential in the fields of human sports health monitoring. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0025] Figure 1 Schematic diagram of the preparation process of MXene / CB-SR@MS sponge.

[0026] Figure 2 (a, b) Scanning electron microscope images of MXene / CB-SR@MS pressure sensor; (c) Image of conductive sponge supported on a blade; (d) X-ray diffraction patterns of CB, MXene, and MXene / CB composites.

[0027] Figure 3 Analysis of the sensing mechanism of MXene / CB-SR@MS pressure sensor.

[0028] Figure 4 (a, b) Pressure-strain curves of MS and MXene / CB-SR@MS sensors; (c) loading-unloading cycle of MXene / CB-SR@MS sensor at 80% strain; (d) pressure-strain curve of MXene / CB-SR@MS after 60 cycles at 40% strain.

[0029] Figure 5 (a) Relationship between relative resistance change of MXene / CB-SR@MS sensor and pressure; (b) IV curves of MXene / CB-SR@MS sensor under different pressures.

[0030] Figure 6 (a) Response / recovery time of MXene / CB-SR@MS sensor; (b) current response of MXene / CB-SR@MS sensor under continuous same pressure; (c) change curve of resistance value after pressure release; (d) repeated loading-unloading response curve.

[0031] Figure 7 (a) Wrist pulse detection current signal; (b, c) finger bending detection signal; (d) elbow bending detection signal; (e) human breathing detection signal.

[0032] Figure 8 Schematic diagram and actual picture of the plantar gait detection sensing array based on MXene / CB-SR@MS sensor.

[0033] Fig. 9The resistance response of the plantar gait detection sensor array based on MXene / CB-SR@MS sensor during the walking stage. The five stages are: Ⅰ initial landing stage, Ⅱ support reaction stage, Ⅲ midpoint support stage, Ⅳ late support stage, Ⅴ early swing stage.

[0034] Fig.10 The resistance response of the plantar gait detection sensing array based on MXene / CB-SR@MS sensors during running.

[0035] Fig.11 The resistance response of the plantar gait detection sensing array based on MXene / CB-SR@MS sensors when climbing stairs. DETAILED DESCRIPTION

[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.

[0038] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.

[0039] In the description of the present invention, it is necessary to understand that the terms "middle", "upper", "lower", "ascending", "descending", "vertical", "face", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0040] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.

[0041] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.

[0042] The present invention discloses a MXene-based SR@MS sponge, a preparation method and an application in a flexible wearable pressure sensor.

[0043] Example 1

[0044] A preparation method of a MXene-based SR@MS sponge (MXene / CS-SR@MS sponge) is as follows:

[0045] 1) Materials

[0046] The chemical raw materials used are silicone rubber, carbon black, tris(hydroxymethyl)aminomethane, hydrochloric acid (analytical grade), naphtha, lithium fluoride (≥98%), titanium aluminum carbide powder and dopamine hydrochloride. All chemicals can be used without further purification, and the water used is deionized water.

[0047] 2) Preparation of MXene / CB composite solution

[0048] ① LiF / HCl solution is used to chemically etch Ti3AlC2 in order to synthesize MXene nanosheets with uniform structure. The detailed preparation process is as follows:

[0049] In the initial stage, 2 grams of LiF were mixed with 20 mL of 9M hydrochloric acid and stirred for 5 minutes under magnetic stirring to ensure adequate mixing. In order to accurately control the temperature of the reaction system and avoid excessive temperature due to exothermic reaction, the etching solution was cooled in a water bath containing ice cubes. Then, 2 grams of Ti3AlC2 were added to the pre-cooled mixed solution in small batches, and the temperature of the overall reaction mixture was maintained at 35°C. This measure was to alleviate the drastic temperature fluctuations that may be caused by the exothermic reaction. In addition, continuous stirring was ensured for 24 hours in the temperature range of 40 to 50°C, while maintaining proper ventilation of the container to exhaust possible gases. After the reaction was completed, the reaction mixture was washed several times with deionized water and centrifuged at 3500 rpm for 5 minutes. This step was repeated until the pH value of the supernatant stabilized at 6. Thereafter, the resulting precipitate was collected and redispersed in deionized water, and ultrasonic treatment was performed for 1 hour under argon protection, while an ice water bath was used to prevent possible heat accumulation during the ultrasonic process from causing irreversible damage to the sample. The last step was to separate and collect the supernatant by centrifugation at 3500 rpm for 1 h to obtain the desired high-purity MXene nanosheet solution.

[0050] ② Adsorption of CB nanoparticles on MXene nanosheet solution

[0051] The mass ratio of CB, deionized water and MXene solution was 0.1:10:5; the concentration of MXene solution was 10 mg / mL, CB and MXene were mechanically stirred in a ratio of 2:1 for 30 min and then ultrasonically treated for 15 min to obtain a well-dispersed MXene / CB composite solution.

[0052] 3) Preparation of PDA-MS porous sponge

[0053] The MS cubes were washed with ethanol and water respectively and dried in an oven at 50°C for 1 hour. Tris(hydroxymethyl)aminomethane was dissolved in distilled water, the pH value was kept at 8-9, and dopamine (DA) was added and dissolved. The cleaned MS was immersed in the above solution at room temperature for 2 hours. Under the action of tris(hydroxymethyl)aminomethane, DA self-polymerized on the surface of the MS skeleton and formed a polydopamine (PDA) adhesion layer to obtain a PDA-MS sponge.

[0054] 4) Preparation of MXene / CS-SR@MS sponge

[0055] After the PDA-MS was transferred to a drying oven at 50°C and dried for 2 hours, it was thoroughly soaked in the MXene / CB composite solution and dried at 50°C. The PDA on the sponge surface and the MXene / CB composite material had a strong mutual bonding effect. Next, the MS was soaked in the SR / naphtha solution for 15 seconds and suspended in the air to drain the excess solution to form a uniform covering layer on the surface of the sponge skeleton. The MS was then thoroughly soaked in the MXene / CB composite solution and the SR / naphtha solution and cured at 80°C for 6 hours. In this process, the cured SR layer acts as a connecting skeleton between the MXene / CB and the MXene / CB. Repeat the above steps to achieve the purpose of layer-by-layer self-assembly to obtain the MXene / CS-SR@MS sponge.

[0056] 5) Sensor structure analysis and characterization

[0057] The morphology of the samples was characterized by scanning electron microscopy. Figure 2 -a and Figure 2 As shown in Figure 2-b, the interior of the MXene / CS-SR@MS sponge is a typical porous grid structure with a skeleton diameter of about 5 to 10 μm. The good coating of SR provides good protection for the sensing material. Figure 2 -c shows the outstanding weight advantage of MXene / CB-SR@MS pressure sensor, even a single blade can support the sensor without any deformation. The physical composition of the sensing materials (CB, MXene and MXene / CB) was characterized by X-ray diffraction technology, such as Figure 2 The characteristic peak at 6.36° of the MXene / CB composite material is mainly attributed to MXene, and the characteristic peaks near 25° and 40° belong to the (002) and (100) planes of CB, respectively, which illustrates the existence of CB and MXene and the successful preparation of MXene / CB composite materials.

[0058] Example 2

[0059] The preparation method of a MXene-based SR@MS sponge (MXene / CB-SR@MS sponge) is the same as that in the above-mentioned Example 1, except that the drying temperature is 60° C., and the other steps are the same.

[0060] Example 3

[0061] A method for preparing a MXene-based SR@MS sponge (MXene / CB-SR@MS sponge) is the same as that in Example 1 above, except that the drying temperature is 70°C, and the remaining steps are the same.

[0062] 1. Sensing mechanism and performance test of MXene / CB-SR@MS flexible wearable pressure sensor

[0063] 1) Sensor sensing mechanism

[0064] The MXene / CB-SR@MS sponge pressure sensor was prepared by impregnating MXene / CB composite solution and SR / naphtha solution through PDA modification and layer-by-layer self-assembly method and drying, and the electrodes were encapsulated on the upper and lower sides of the sponge to complete the device preparation. Figure 3 The sensing mechanism of the MXene / CB-SR@MS pressure sensor was revealed. In the initial state, when no pressure was applied to the MXene / CB-SR@MS sensor, the inside of the sponge showed a honeycomb-like 3D grid connection structure. The conductive sensitive materials on the skeleton only contact each other at the connection points of different skeletons. In this state, the number of conductive paths inside the sensor is limited. When pressure begins to be applied to the sensor, that is, in the first working area, the MS is slightly deformed, and the connection between some skeletons is disconnected, resulting in the disconnection of some conductive sensitive materials that were originally in contact with each other, so the conductive path is reduced to a certain extent, and the resistance value of the MXene / CB-SR@MS sensor increases. When the external pressure gradually increases, the sponge deformation continues to increase, and the air in the sponge pores is squeezed out in large quantities. At this time, the sensor works in the second area, the sponge skeleton begins to collapse, and the gaps begin to gradually decrease. Many sponge skeletons contact each other, and the conductive sensitive materials attached to the sponge skeleton begin to contact, generating a large number of conductive contact sites, thereby forming more conductive paths, and the overall conductivity of the sensor increases, causing the resistance value of the MXene / CB-SR@MS sensor to begin to decrease.

[0065] 2) Sensor performance test

[0066] (1) Mechanical properties test

[0067] Evaluation of the mechanical properties of flexible pressure sensors is crucial because it needs to maintain good flexibility and excellent mechanical properties. Figure 4 -a is the pressure-strain curve of MS without sensitive materials attached, and the curve can be divided into three stages. The first stage is when the strain is less than 20%, and the pressure increase mainly comes from the resistance between the sponge skeletons. The second stage is the 20% to 60% strain stage. At this time, the pressure increase rate is significantly slower than the first stage. This is because the pressure increase in this stage mainly comes from the compression of the porous skeleton inside the sponge. The third stage is when the strain is greater than 60%, the pressure increases rapidly, because the air in the pores inside the sponge is basically discharged.

[0068] Figure 4 -b is the pressure-strain curve of the MXene / CB-SR@MS sensor. Under the same strain, the pressure of the MXene / CB-SR@MS sensor is significantly greater than that of pure MS. Figure 4 -c, the pressure hysteresis of the sensor is 21.7%. Figure 4 -d is 40% strain, and the MXene / CB-SR@MS pressure sensor is subjected to 60 consecutive loading-unloading tests. It can be seen that the pressure curve of the sponge decreases slightly when it is loaded, which is due to the relaxation characteristics of the sponge as a porous block structure, but the pressure curves when unloading are basically the same, and the pressure values ​​when reaching 40% strain are almost the same, which is due to the enhancement of the mechanical properties of the sensor by the modified sponge and SR buffer layer.

[0069] (2) Sensing performance test

[0070] Figure 5 -a reflects that the response of the sensor's electrical signal can be divided into four parts. When the pressure is lower than 2kPa, due to slight deformation of the MS, the connection between some skeletons is disconnected, resulting in the disconnection of the conductive sensitive materials that were originally in contact with each other, and the reduction of conductive contact sites, which slightly increases the sensor resistance. When the pressure is 2-20kPa, the collapse of the sponge skeleton causes the internal pores to shrink rapidly, and the conductive materials on the inner walls of the pores contact each other, creating more conductive paths, resulting in a significant reduction in resistance. Because of the existence of pores, the sensor can show an obvious resistance signal response without applying a large force, so the sensitivity reaches its peak at this stage (7.44kPa -1 ). When the pressure is 20-80kPa, the contact between different sponge skeletons is relatively sufficient. As the pressure increases, the skeleton body is also compressed. At this time, the increase in conductive sites inside the sponge only comes from the contact between sensitive materials between different skeletons. The number of increased conductive paths decreases, and the sensitivity decreases rapidly. When the pressure is greater than 80kPa, the sponge skeleton is almost completely in contact. Figure 5 -b is the current signal diagram of the MXen / CBe-SR@MS pressure sensor when a voltage signal of -1V to 1V is applied under different pressures. The slope of the curve increases with the increase of pressure. When the pressure is small, the slope of the IV curve changes slowly. When the pressure remains unchanged, the slope of the curve remains basically unchanged, indicating that the sensor has good linearity and reliability.

[0071] Figure 6 -a reflects that the response time and recovery time of the sensor are 150ms and 180ms respectively. When the pressure is released, the current quickly reaches the initial value and remains stable. This shows that the sponge sensor can quickly release the internal potential energy after the pressure is released, and there is less pressure relaxation.

[0072] from Figure 6 -b It can be seen that after repeated compression of the sensor, the current returns to its initial value and is relatively stable. In order to determine whether the sensor has creep, pressure is applied to the sensor and maintained for a certain period of time ( Figure 6-c), it can be found that the resistance value of the sensor has changed. According to the definition of creep (ΔR / time), the creep of the sensor is 0.31.

[0073] 3700 loading-unloading tests were performed at 10 kPa ( Figure 6 -d). After long-term loading, the resistance response of the sensor remains stable, indicating that the sensor has excellent stability and broad application prospects. Compared with other sponge pressure sensors, the MXene / CB-SR@MS sensor has the advantages of large measurement range and high sensitivity.

[0074] 2. Application research of MXene / CB-SR@MS flexible wearable pressure sensor

[0075] 1) Human physiological signal detection

[0076] MXene / CB-SR@MS sensors have the performance advantages of wide measurement range and high sensitivity, and can be used to detect various human motion signals. In this type of test, PI tape is used to encapsulate the sensor on the skin contact surface and the side of the sensor to ensure that the tester's skin does not touch the sensitive material. Figure 7 -a, the sensor is fixed to the radial artery of an adult male wrist with insulating tape, and a relatively stable current response waveform can be received. Analysis and calculation of the waveform show that the tester's pulse signal frequency is 78 times / min, which is in the normal range under a calm state. The three characteristic peaks of the pulse in the enlarged waveform in the figure, namely the shock wave (P), tidal wave (T) and diastolic wave (D), can be used to evaluate the cardiovascular health of the human body. The sensor's response to finger bending was also investigated.

[0077] Figure 7 -b and Figure 7 -c reflects that as the degree of finger bending increases, the sensor resistance response increases. Therefore, by judging the size of the response signal, the bending of the finger can be easily determined. In addition, the MXene / CB-SR@MS sensor also has good repeatability at the same finger bending angle. In addition, the sensor can also detect the pressure signal when the elbow is bent ( Figure 7 -d).

[0078] Small strain motion monitoring based on micro-pressure signals is also particularly important in the detection of human physiological signals. Figure 7 -e is a sponge sensor fixed on the mask to monitor the deep and shallow breathing behavior of the human body. The breathing action will cause the mask to deform slightly, which will then exert pressure on the sensor. According to the frequency of the response signal, it can be judged whether the tester is taking deep or shallow breaths and the specific frequency index of breathing. The above results reflect the potential value of this sensor in the application of human physiological movement detection system.

[0079] 2) Human gait signal detection

[0080] Six MXene / CB-SR@MS sensors were distributed in the heel, midfoot, and forefoot, defined as S1 to S6. Since there are fewer pressure application sites in the midfoot and heel during gait, one sensor was placed in each. In the forefoot, four sensors were placed to improve the resolution of foot pressure measurement at the initial and final stages of walking, which plays a key role in analyzing gait ( Figure 8 ). In addition, the ultra-low density of the sponge will not bring extra burden to the tester's feet and cause gait changes.

[0081] During walking, a gait cycle consists of five phases: initial landing phase, support reaction phase, midpoint support phase, late support phase, and early swing phase. Fig. 9 The dynamic response of the plantar gait detection sensor array based on MXene / CB-SR@MS sensors (the swinging leg is the dark leg in the figure). The response time of the sensor during walking is about 0.1 to 0.2 seconds.

[0082] Running is a similar sport to walking, but at a faster pace. With a smaller stride frequency, the sole of the foot is subjected to greater pressure and exhibits a greater resistance response. The heel strike is more instantaneous when running compared to walking. Fig.10 This reflects that the time taken for a cycle from the start to the end of the movement is shorter, indicating that the foot is on the ground for a short time.

[0083] Fig.11 This is the detection of the stair climbing state. First, the whole sole of the foot is shown on the ground, but the resistance response of the sensors in different parts of the forefoot is different. In other stages, the pressure on the forefoot is similar to that in the walking state, and the forefoot is under greater pressure than the midfoot and heel, so the resistance response of the sensor is also higher than that in the walking state. Compared with other walking states, the bending of the human foot will be significantly reduced when climbing stairs, which is reflected in the output of the sensor as a more obvious step-like resistance response.

[0084] Based on the above analysis, it can be seen that the present invention modifies MS by PDA and prepares an ultra-low density MXene / CB-SR@MS pressure sensor by layer-by-layer self-assembly method. SR is used as a buffer layer to improve the mechanical properties of the flexible pressure sensor, and MXene and CB composite materials are used to improve the conductivity of the sensor. The measurement range of the MXene / CB-SR@MS sensor is up to 240kPa, the sensitivity is 7.44kPa-1, and excellent repeatability (more than 3700 cycle tests) is obtained. The SR hybrid sponge and self-assembly method make CB and MXene more stably adhere to the sponge skeleton, ensuring that the conductive sponge maintains good reproducibility in a large number of repeated tests. The porous skeleton inside the sponge enables the sensor to detect human body movements under various pressures, including pulse, finger bending, elbow bending and breathing, without interfering with the normal movement of the human body. In addition, a distributed sensing array is developed based on the MXene / CB-SR@MS sensor to detect multiple walking states. In summary, the MXene / CB-SR@MS flexible pressure sensor has great application potential in human motion monitoring, health detection and wearable electronic devices.

[0085] The stability and reliability of MXene / CB-SR@MS flexible pressure sensors bring possibilities for human physiological detection and motion monitoring. In short, MXene / CB-SR@MS sponge flexible pressure sensors have great application potential in smart wearable devices and human motion detection.

[0086] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A MXene-based SR@MS sponge, characterized in that: The MXene-based SR@MS sponge is a MXene / CB-SR@MS sponge, which is prepared by coating a MXene / CB composite material on a SR@MS sponge skeleton by a solution impregnation and low-temperature drying method; The MXene / CB composite material is CB nanoparticles deposited on MXene nanosheets by electrostatic adsorption, and the MXene nanosheets are obtained by selectively etching Ti3AlC2 with hydrochloric acid / lithium fluoride etching solution.

2. A method for preparing a MXene-based SR@MS sponge as claimed in claim 1, characterized in that: The method specifically comprises the following steps: 1) Ti3AlC2 is first selectively etched with hydrochloric acid / lithium fluoride etching solution to obtain MXene nanosheets, and then a dispersed MXene solution is obtained by ultrasound and centrifugation; 2) stirring the CB nanoparticles in deionized water, then adding the MXene solution prepared in step 1) and mixing thoroughly, heating and stirring to obtain a MXene / CB composite solution for later use; 3) dissolving tris(hydroxymethyl)aminomethane in distilled water, and adding dopamine (DA) to stir and dissolve; placing MS in the solution, under the action of tris(hydroxymethyl)aminomethane, DA self-polymerizes on the surface of the MS skeleton and forms polydopamine PDA, thereby obtaining PDA-modified MS; 4) The SR@MS porous sponge prepared in step 3) is immersed in the MXene / CB composite solution obtained in step 2), and then immersed in the SR / naphtha solution, dried and repeated, so as to coat the MXene / CB composite material and SR on the SR@MS sponge skeleton by a layer-by-layer self-assembly method, and finally obtain a MXene / CB-SR@MS sponge, i.e., the MXene-based SR@MS sponge.

3. The method for preparing the MXene-based SR@MS sponge according to claim 2, characterized in that: In step 1), the operation of selectively etching Ti3AlC2 with hydrochloric acid / lithium fluoride etching solution to obtain MXene nanosheets is as follows: Ti3AlC2 was added in batches to a pre-cooled LiF / HCl solution and stirred for reaction. The solution was then washed and centrifuged until the pH value of the supernatant was stabilized at 5-7. The resulting precipitate was dispersed in deionized water and sonicated under argon protection. The supernatant was centrifuged, separated, and collected to obtain a high-purity MXene nanosheet solution.

4. The method for preparing the MXene-based SR@MS sponge according to claim 3, characterized in that: In the LiF / HCl solution, the mass ratio of lithium fluoride to hydrochloric acid is 1:(4.8-5.2); the mass ratio of the LiF / HCl solution to Ti3AlC2 is (5.2-5.5):1, and the temperature of the entire reaction mixture is maintained at 40°C-50°C, and continuous stirring is ensured within this temperature range for 24 hours.

5. The method for preparing the MXene-based SR@MS sponge according to claim 2, characterized in that: In step 2), the mass ratio of the CB to MXene solution is (0.1-0.5):5; the concentration of the MXene solution is 10 mg / mL, and the mass ratio of CB to MXene nanosheets is (2-10):1; the MXene / CB mixed solution is mechanically stirred for 30-60 min, and then ultrasonically treated for 15-30 min.

6. The method for preparing the MXene-based SR@MS sponge according to claim 2, characterized in that: Dissolve tris(hydroxymethyl)aminomethane in distilled water and keep the pH value at 8-9; immerse MS in the solution at room temperature for 1-3 hours. Under the action of tris(hydroxymethyl)aminomethane, DA self-polymerizes on the surface of the MS skeleton and forms a polydopamine (PDA) adhesion layer.

7. The method for preparing the MXene-based SR@MS sponge according to claim 2, characterized in that: In step 4), in the SR / naphtha solution, the mass ratio of silicone rubber to naphtha is (1-3):1; the immersion time is 0.5-2h, the drying temperature is 60-80°C, and the drying time is 4-8h.

8. Use of the MXene-based SR@MS sponge as claimed in claim 1 or the MXene-based SR@MS sponge prepared by the method as claimed in claim 2 in a flexible wearable pressure sensor.

9. The use according to claim 8, characterized in that: The MXene-based SR@MS sponge can be used in flexible wearable pressure sensors for detecting human physiological signals.

10. The use according to claim 8, characterized in that: The MXene-based SR@MS sponge can be used in wearable sensors for detecting joint movements in various parts of the human body.

Citation Information

Patent Citations

  • MXene@CS@PDMS three-dimensional porous composite material and preparation method and application thereof

    CN110375894A

  • Wearable bionic pressure-resistance sensor and preparation method and application thereof

    CN111442861A

  • Flexible piezoresistive pressure sensor based on two-dimensional titanium carbide / polyaniline as well as preparation method and electronic skin sensing application of flexible piezoresistive pressure sensor

    CN115028887A

  • Giant magnetoelastic self-powered pressure sensor for biological monitoring

    CN118302658A

  • Flexible hydrogel based on MXene, preparation method and application of flexible hydrogel in pressure sensor

    CN118725201A